2013
DOI: 10.3109/17435390.2012.763147
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of nephrotoxicity of intravenously administered sodium-oleate-coated ultra-small superparamagnetic iron oxide (USPIO) and titanium dioxide (TiO2) nanoparticles in rats

Abstract: As a main excretory organ, kidney is predisposed to direct/indirect injury. We addressed the potential nephrotoxic effects following expositions of healthy rats to nanoparticle (NP) loads relevant to humans in a situation of 100% bioavailability. Up to 4 weeks after administration, a single iv bolus of oleate-coated ultra-small superparamagnetic iron oxide NPs (in dose of 0.1%, 1.0% and 10.0% of LD50) or TiO2 NPs (1.0% of LD50) did not elicit decline in renal function, damage to proximal tubules, alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 85 publications
1
19
0
Order By: Relevance
“…OC-Fe 3 O 4 NP deposits were clearly seen in whole liver parenchyma in contrast to Magnetic Resonance Imaging (MRI) of the kidney, confirming that liver is the main target organ of these NPs. Highest TiO 2 NPs levels were revealed also in liver, followed by spleen, and lung (Sebekova et al, 2014). The data reported by Volkovova et al (2015) suggest that the liver likely retains functional integrity with sub-lethal doses of OC-Fe 3 O 4 NPs, albeit with some stimulation of redox defences and evidence of some tissue injury shortly after the injection.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…OC-Fe 3 O 4 NP deposits were clearly seen in whole liver parenchyma in contrast to Magnetic Resonance Imaging (MRI) of the kidney, confirming that liver is the main target organ of these NPs. Highest TiO 2 NPs levels were revealed also in liver, followed by spleen, and lung (Sebekova et al, 2014). The data reported by Volkovova et al (2015) suggest that the liver likely retains functional integrity with sub-lethal doses of OC-Fe 3 O 4 NPs, albeit with some stimulation of redox defences and evidence of some tissue injury shortly after the injection.…”
mentioning
confidence: 55%
“…The data reported by Volkovova et al (2015) suggest that the liver likely retains functional integrity with sub-lethal doses of OC-Fe 3 O 4 NPs, albeit with some stimulation of redox defences and evidence of some tissue injury shortly after the injection. Data on nephrotoxicity were published previously (Sebekova et al, 2014) showing mild or no effect and the majority of results addressing other organ and tissue toxicity are under preparation.…”
mentioning
confidence: 99%
“…Sodium-oleate-coated USPIO have been studied in vivo in a rat model administered as a single dose at varying concentrations and followed for 1 month. There was no change in renal function or cellular morphology 116 . While these studies highlight some of the properties of NPs and how they may affect the kidney, there exist no in vivo human studies that particularly investigate the toxicology profiles of these biological NPs.…”
Section: Nephrotoxicity Of Nanoparticlesmentioning
confidence: 86%
“…The current knowledge regarding the effect of NP size on biological systems is still incomplete. However, NP properties associated with particle size are crucial factors that determine the biological safety of NPs, and can directly affect feasibility of NP in biomedical applications (Alarifi et al, 2014;Šebeková et al, 2014). The study of nanotoxicology has shown that NPs with the same composition but different magnetic surface charge can produce toxic damage (Kut et al, 2012;Ma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%